The Heian Court Poetry as World Literature From the Point of View of Early Italian Poetry - GERLINI, Edoardo (Strumenti per la didattica e la ricerca, 2014)
What could be the common points between the Literature produced at the imperial court of 9th-10th century in Japan with the one composed in Italy under the rule of Frederick II of Hohenstaufen? Why the Kokinwakashū in Japan and the Sicilian School of Poetry in Italy have been acknowledged as canons for later literary traditions? How did the political power influence the production of court poetry and the role of poets in the court environment? Why two particular poetic forms like the sonnet in Europe and the waka in Japan succeeded to survive until modern times?